Studying Transnational and Translingual Professional Communication - Suresh Canagarajah (Polylinguality and Transcultural Practices)
In the modern world of globalization, there is a need to establish a multilingual communication environment in the work process of transnational corporations for more efficient execution of tasks and organization of negotiations. As a result, a completely new polylingual space appears with its own internal dynamics of linguistic phenomena, the study of which requires the formation of new approaches to research. In this paper, the processes that arise as a result of the transition of business to a transnational space are analyzed from the point of view of Interactive Sociolinguistics. The influence of global processes and technologies on communication and inter-action between participants in work and contractual processes within corporations and between them is considered. The formation of a multilingual communication system due to the participation of users of different languages in communication is studied. The factors that result in the establishment of a particular multilingual system in the workspace are identified, and its manifestations are considered. The internal dynamics of this system are studied as it develops. The work is based on theoretical and practical researches by authoritative authors in the field of sociolinguistics, such as J.J. Gumperz, R. Wodak, J. Blommaert, and others. The study analyzes the effectiveness of the application of the Interactive Sociolinguistics approach to describing the work process in the context of the need to establish multilingual communication in transnational business.